NLRP3 deficiency protects from type 1 diabetes through the regulation of chemotaxis into the pancreatic islets - Hu, Changyun; Ding, Heyuan; Li, Yangyang; Pearson, James A.; Zhang, Xiaojun; Flavell, Richard A.; Wong, F. Susan; Wen, Li (Proceedings of the National Academy of Sciences - PNAS, 2015)
Studies in animal models and human subjects have shown that both innate and adaptive immunity contribute to the pathogenesis of type 1 diabetes (T1D). Whereas the role of TLR signaling pathways in T1D has been extensively studied, the contribution of the nucleotide-binding oligomerization domain, leucine-rich repeat and pyrin domain-containing protein (NLRP) 3 inflammasome pathway remains to be explored. In this study, we report that NLRP3 plays an important role in the development of T1D in the nonobese diabetic (NOD) mouse model. NLRP3 deficiency not only affected T-cell activation and Th1 differentiation, but also modulated pathogenic T-cell migration to the pancreatic islet. The presence of NLRP3 is critical for the expression of the chemokine receptors CCR5 and CXCR3 on T cells. More importantly, NLRP3 ablation reduced the expression of chemokine genesCCL5andCXCL10on pancreatic islet cells in an IRF-1–dependent manner. Our results suggest that molecules involved in chemotaxis, accompanied by the activation of the NLRP3 inflammasome, may be effective targets for the treatment of T1D.